MENINGKATKAN KREATIVITAS SISWA MELALUI MODEL PEMBELAJARAN KONTEKSTUAL PADA MATERI MENGGAMBAR FLORA, FAUNA DAN ALAM BENDA DI KELAS VII SMP NEGERI 3 RAMBAH HILIR - Erni Yulita (JURNAL PENDIDIKAN ROKANIA, 2019)
his study aims to improve the creativity of class VII.A students in Cultural Arts subjects in drawing Flora, Fauna and Nature in SMP Negeri 3 Rambah Hilir in the academic year 2016/2017. This research was carried out for two cycles. The subjects of this study were students of class VII-I of SMP Negeri 3 Rambah Hilir, amounting to 28 students. Based on the results of the study through contextual learning models can increase creativity in the subjects of Cultural Arts and Skills in drawing Flora, Fauna and Nature. From the results of the picture students showed improvement. In the first cycle there was an increase with an average value of 60.3 and in the second cycle also increased from an average value of 63.63 to 64.78. Completeness in drawing illustrations of students in cycle II increased by 100%.